Improved electrochemical performance of rare earth doped LiMn1.5-xNi0.5RExO4 based composite cathodes for lithium-ion batteries - Ram, Pura (2018)
LiMn1.5Ni0.5O4 with spinel type of structure was synthesized by sol-gel method and doped by different rare-earth elements (Nd, Gd and Dy). It was found that the inclusion of rare-earth element preserves the cubic spinel structure, leads to smaller particle size and improves the cyclic performance of the produced batteries. The best battery performance was obtained after doping the spinel structure by Gd. Among the used rare-earth elements Gd is the only one with stable oxidation state of 3 + which leads to stabilization of the Mn dissolution.Thus, the improvements observed in battery performance (rate performance and cycle life) are due to the superior structural stability of the doped active materials. It is concluded that the LiMn1.48Ni0.5Gd0.02O4 sample is the one with the best overall performance to act as active material for cathodes in rechargeable lithium-ion batteries.